Efektivitas Allicin Bawang Putih terhadap Fusarium oxysporum f. sp. raphani pada Lobak In Vitro: Systematic Literature Review - Najwa Luthfiah Khanza (Jurnal Kridatama Sains dan Teknologi, 2026)
Fusarium wilt caused by Fusarium oxysporum f. sp. raphani is one of the major constraints in radish cultivation, as it infects the plant vascular system and leads to significant yield losses. Conventional control methods mainly rely on synthetic fungicides; however, their long-term use may cause environmental damage and the development of pathogen resistance. Therefore, there is a need for environmentally friendly alternatives such as allicin derived from Allium sativum L. This study aims to evaluate the effectiveness of allicin as a biological control agent against F. oxysporum f. sp. raphani using a systematic literature review approach. This study employed a qualitative method based on a systematic literature review of 18 relevant scientific articles. Data were analyzed using thematic analysis focusing on antifungal activity, mechanisms of action, and concentration effectiveness of allicin. The data sources were obtained from peer-reviewed journals, both national and international, indexed in reputable scientific databases. The synthesis results indicate that allicin exhibits significant antifungal activity against Fusarium spp. through sulfhydryl (-SH) enzyme inhibition, oxidative stress induction, and disruption of fungal cell membranes. Its effectiveness is influenced by concentration and extraction methods. However, specific studies on F. oxysporum f. sp. raphani remain limited, indicating a research gap. In conclusion, allicin has strong potential as an environmentally friendly biological control agent for inhibiting the growth of F. oxysporum f. sp. raphani. This study contributes to the development of sustainable plant disease management strategies based on natural compounds